2020
DOI: 10.1002/dc.24444
|View full text |Cite
|
Sign up to set email alerts
|

Does cervicovaginal cytology have a role in the diagnosis and surveillance of endometrial adenocarcinoma?

Abstract: Objective To examine the role of cervicovaginal cytology in diagnoses and surveillance of the patients with endometrial carcinoma (EC). Methods Patients who underwent EC surgery that included a follow‐up were reviewed retrospectively. The cohort was limited to the patients who had an available cervical cytology result within 12 months before the primary surgery took place. The glandular abnormalities were classified in the following subclassifications: “atypical glandular cells” (AGC)‐not otherwise specified (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our study, the same conclusion was not reached, which may be because many factors, such as comorbidities, abnormal vaginal bleeding, and endometrial thickness, were included in our analysis. A review of cervical cytology in patients with endometrial cancer found that the detection rate of abnormal cervical cytology for endometrial cancer was 10.5%-31.7% [12][13][14] . In this study, there were 7 cases of endometrial atypical dysplasia/endometrial cancer, accounting for 4%, because our inclusion criteria were patients with endometrial cells found in cervical cytology rather than all patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the same conclusion was not reached, which may be because many factors, such as comorbidities, abnormal vaginal bleeding, and endometrial thickness, were included in our analysis. A review of cervical cytology in patients with endometrial cancer found that the detection rate of abnormal cervical cytology for endometrial cancer was 10.5%-31.7% [12][13][14] . In this study, there were 7 cases of endometrial atypical dysplasia/endometrial cancer, accounting for 4%, because our inclusion criteria were patients with endometrial cells found in cervical cytology rather than all patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%